2010
DOI: 10.1007/s11258-010-9735-8
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Robinia pseudoacacia riparian forests after clear-cutting along the Chikumagawa River in Japan

Abstract: Regeneration processes of riparian Robinia pseudoacacia forests after clear-cutting were investigated through dendroecological and microsatellite polymorphism analyses. Age determination of regenerated R. pseudoacacia trees based on the dendroecological analysis revealed that forests regenerating after clear-cutting were composed of trees that mostly established within a few years after clear-cutting. This suggests that the stimulus to form new shoots was evoked by clear-cutting but faded within a few years. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…In our previous study, various sizes of R. pseudoacacia genets were found to have four nuclear SSR markers (Kurokochi et al 2010). This result supported the fine-scale role of asexual reproduction in the formation of R. pseudoacacia riparian forests; however, the extent to which sexual reproduction contributes has yet to be determined.…”
Section: Study Site and Sample Collectionsupporting
confidence: 57%
See 2 more Smart Citations
“…In our previous study, various sizes of R. pseudoacacia genets were found to have four nuclear SSR markers (Kurokochi et al 2010). This result supported the fine-scale role of asexual reproduction in the formation of R. pseudoacacia riparian forests; however, the extent to which sexual reproduction contributes has yet to be determined.…”
Section: Study Site and Sample Collectionsupporting
confidence: 57%
“…We demonstrated that, within several years of clear-cutting activity, most R. pseudoacacia trees became established through asexual reproduction. In addition, we observed that some R. pseudoacacia trees regenerated asexually around a fallen R. pseudoacacia tree (Kurokochi et al 2010). Our results indicate that an established R. pseudoacacia tree of a certain nuclear genotype could maintain its genotype in the forest.…”
Section: Study Site and Sample Collectionmentioning
confidence: 76%
See 1 more Smart Citation
“…This finding is consistent with our observations. Also, in case of Robinia pseudoacacia which reproduces both sexually and asexually (Kowarik 1996, Jung et al 2009, Kurokochi et al 2010, some studies have shown that new horizontal roots are supplied with photosynthates from the mother plant or ramet for a few years only and that resource translocation between neighboring ramets within the same clone ceases after several years (Jung et al 2009). This might explain the advantage of root sprouts in the initial period of their development.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear microsatellite (nSSR) markers with high polymorphism can contribute to the analysis of parenthood, kinship, and population differentiation (Kurokochi and Hogetsu 2014). The capability of asexual reproduction of woody species via adventitious roots could form large genets with a lot of ramets (Gyokusen et al 1991, Kowarik 1995, Ogawa and Hukusima 1996, Kurokochi et al 2010, and genets can be readily detected with high polymorphism nuclear DNA markers (Jung et al 2009, Kurokochi et al 2010). ABI 3130 automated DNA sequencer (Applied Biosystems, Foster City, CA, USA), and their fragment sizes were analyzed with a GeneMapper software (Applied Biosystems).…”
Section: Site Patch and Sample Collectionmentioning
confidence: 99%